Influence of Marketing Strategy on Members Saving Interests Study at BMT Ta'awun Jambu Sumedang - Rahmawati, Citra; Umayah, Ulfa Nur; Purwanti, Neli (International Journal of Sharia Business Management, 2024)
The background of this study is that the community is still not interested in using BMT products or services, even though BMT has implemented marketing strategies according to community needs. The question is why the community is not interested in becoming a member of BMT. The formulation of the problem of this study is how is the marketing strategy in BMT Ta'awun, how does the marketing strategy affect the interest in saving members. The population of all members of BMT Ta'awun Jambu Sumedang totaling 9,923 members and a sample of 99 members, data collection techniques through interviews, documentation, questionnaires or questionnaires. The results of the study showed that marketing strategies did not have a significant effect on members' interest in saving at BMT Ta'awun. The percentage contribution of changes in marketing strategies to members' interest in saving was 3% (very small). The level of closeness of the relationship between marketing strategies and members' interest in saving was very low (r = 0.058). This study is expected to be useful for the development of further research in order to improve the function of marketing strategies as a factor that can increase members' interest in saving at BMT.